Sikap Pelajar Kawruh Jiwa Menghadapi Pandemi Covid-19 - Sunarno; Ashar, Achmad Baharudin; Azizah, Lisa Zakia (Happiness: Journal of Psychology and Islamic Science, 2020)
The culture paradoxity of Indonesia as collectivism becomes one of the problems for social distancing policy during Covid-19 pandemic. Most of cases such as family gathering tradition, mass prayer event or other activities triggering density still occurs as a local habit. By understanding culture and behaviour, this research explores the uniqueness of learners from Kawruh Jiwa Ki Ageng Suryomentaram facing Covid-19 pandemic. The research aims to acknowledge the local wisdom attitudes of learners against crisis situation. Using a qualitativephenomenology method, this research employs four authoritative participants of Kawruh Jiwa and collects data with online interview. The result reveals that all participants show different dynamics of â€œolah rasaâ€ but they still lead to experience of â€œtatagâ€ (resilience). We expect that the existence of Kawruh Jiwa perspective can be a psychological recommendation for encouraging behaviour and mental resilience during pandemic diseases even in the future.